Neonatal transfusion-related acute lung injury a rare complication of exchange transfusion - A case report - Singh, Ranjana; Atul Kumar Saroj (Asian Journal of Medical Sciences, 2023)
Transfusion-related acute lung injury (TRALI), a life-threatening condition, remains an under reported complication, especially among neonates postexchange transfusion for unconjugated hyperbilirubinemia. Appropriate recognition and prompt treatment change the prognosis for good. The present case emphasizes that TRALI must be kept as a differential diagnosis in previously well neonates presenting with sudden onset hypoxia within or during 6 h of transfusion with evidence of bilateral infiltrates on a frontal chest radiograph, and no evidence of circulatory overload, left atrial hypertension, or pre-existing respiratory distress before transfusion. We report the rare occurrence of TRALI and its successful management with supportive hemodynamic management and corrective ventilator strategies.